(POSTER) LEUTINIZED THE COMA IN A POSTMENOPAUSAL WOMAN - Kaluarachchi, A; Marasinghe, J.P; Bacha, T.M; Agunanoel, P (My University)
A 58-year-old woman, presented with progressive androgenization including virilisation, and hypertension. On clinical examination she had a Ferriman Gallway score of 10 and clitaromegaly. Vaginal examination revealed a right adnexal mass of approximately 4cm diameter. Her total serum testosterone level was 4.5ng/ml (normal range 0.06- 0.82) and free testosterone level was 16.6 pg/ml (normal range 0.1- 1.7 and was not suppressed with dexamethasone. Ultrasound scan and C T scan of abdomen & pelvis confirmed the presence of a solid ovarian mass while the adrenal glands were normal. She had total abdominal hysterectomy, bilateral salpingo - oophorectomy and infracolic omentectomy. Histopathological examination revealed a leutinised thecoma of the right ovary. Postoperatively the testosterone level returned to normal and the patient had regression of virilism. Ovarian thecoma is a rare benign tumor of stromal cell origin, and represents less than 1% of all ovarian tumors. It occurs most often in perimenopausal and postmenopausal women. Typical thecomas are almost always estrogenic; the luteinized forms are virilizing in about 10% o f cases. We report a case of a 58-year-old post menopausal woman with a right ovarian leutinised thecoma with progressive virilization. Only 35 reported cases were identified by Search of indexed literature from 1966 - 2007,out of which only one was reported in a post postmenopausal female.